M-Health- Can It Improve Indian Public Health System - Davey, Sanjeev; Davey, Anuradha (National Journal of Community Medicine, 2013)
Introduction: The role of Mobile application evaluation in public health (m-health) is now in fact, essential for us to make use of this very fast growing technology in making the bright future of Public health of people. Objectives: To critically analyze the role of Mobile Applications in Public Health (m-health). Materials and methods: A Systematic Review of related studies in literature published till 30th June 2013on role of Mobile-Applications in Public health (m-Health) was done. Results: A wide variety of Mobile health applications are available in Mobile Phone Market with lack of proper Regulation from health care authorities and with variably good results. Conclusions: We must use these applications guardedly weighing its benefits and utility in Public Health as well as capitalize the good prospect and capability of m-health worldwide application in the field of Public Health Globally. This means that we can have a greater access to larger segments of a population in developing countries like India and this can improve the capacity of our India health system to provide quality healthcare, which is in great demand today.